Automated barrier gate system by using RFID (ABGS) - Suriya Morthi, Manivelu (2019)
Automated Barrier Gate System by Using RFID is to develop a system that able to detect the tag that has given to Sekolah Sukan Malaysia Pahang (SSMP) students and staffs who already registered for the vehicle access to SSMP campus and this tag is used for checking in and checking out. This system also able to increase a safety protection in particular secured area and also can prevent unwanted access. However, this system is mainly for students and staffs. When a user scans a tag at the RFID reader when passing by the barrier gate the system will stored the details of users which is name, id number, vehicle number, time and date of access. There is some place that will be still using manually operated barrier gate system. Manually operated barrier gate system will not updating the information of user who is using the system. Besides that, there will be a lot of wasting time since a security guard have to check the user manually whether they are Sekolah Sukan Malaysia Pahang students or staffs or non-user. So that, there will be more cars waiting to pass the gate since manually operated. At the end, the details of users and the time and date will not be taken due to lack of timing. Eventhough, there is some will taking the information by manually writing the details on log book. But if the log book is damaged then there is no saved information. However, with this system, there is no chance to be damaged on saved information in database. The administrator can check at any time the database that stored the information. Therefore, by using this system user can reduce the time of waiting to pass at the entrance gate. This system will able to stored data into the database and the file can be downloaded into other file type which will make the administrators job can be done easier for checking.